India’s Private Universities: Solutions or Problems? - Powar, Krishnapratap B. (International Higher Education, 2015)
In India, private universities are a response to the growing demand, in a demographically young country, for higher education; and the inability of the government to fulfill its social responsibility relating to provision of higher education. For the ‘haves’ they provide a solution to the problem of access. For the ‘have nots’ they are a social evil, responsible for widening the economic and social divide.